A Mytho-Religious Reading of Kumbapattu of the Kurichiya Community of Kerala, India - Dilsha K Das; Preeti Navaneeth (Religions)
Kumbapattu is a folk song of the indigenous Kurichiya community sung during Thira, a religious festival celebrated during the month of Kumbham (February). It narrates the mythical life and actions of Malakkari, an embodiment of Lord Shiva and the chief deity of the Kurichiya. A critical study of this 1051-line folk song, its ritual performance, and its ecological fountainheads can contribute to our understanding of the cultural and ritualistic energies and functions of indigenous art forms. This paper examines the role played by religious folk songs in reiterating Kurichiya identity and community integration, and the relevance of such narratives in addressing ecological challenges while sustaining cultural heritage. The method of close textual analysis of Kumbapattu is employed to decode the religious concepts and philosophies of the community, supplemented by observations of ritual performances during fieldwork. This study draws on both primary and secondary materials for the analysis. The study employs Bronisław Malinowski’s myth–ritual theory to examine the relationship between myth and ritual and their role in shaping the Kurichiya identity. Further, William R. Bascom’s four functional categories are applied to identify the ecological functions expressed through the song, since the community is traditionally agrarian and still largely depends on forest and environment for a significant part of their community life. To provide a culturally grounded interpretation that reflects Kurichiya worldviews, the study also incorporates indigenous epistemology to make the analysis more relevant and comprehensive.